ANALISA PROKSIMAT PAKAN HASIL OLAHAN PEMBUDIDAYA IKAN DI KABUPATEN BANJAR KALIMANTAN SELATAN. - Rina Iskandar; Subhan Fitriadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The purpose of this study is to analyze the proximate feed processed by fish farmers in Banjar district. The research location is in the district of Banjar, South Kalimantan. Using descriptive exploratory method with purposive sampling method. The results showed that the value of the feed proximate test are: Protein (A. 15.37, 15.77 B., C. 16.31, D. 17.09) Fat (7.34 A., B. 6, 72, C. 8.47, D. 10.07). Carbohydrates (A. 36.78, 37.82 B., C. 35.65, D. 43.76). Crude Fiber (A.6,63, 7.74 B., C. 8.12. D. 4,10). The ash content (A. 14.67, 13.00 B., C. 13.43, D. 7.91). The water content (A. 25.84, 26.69 B., C. 26.14, D. 21.17). From these results it can be seen that the protein content of the feed is processed by fish farmers are still below standard protein requirements of fish.